Acquired Cystic Disease-Associated Renal Cell Carcinoma: An Unusual Case in the Absence of Acquired Cystic Disease or Dialysis. (28th October 2020) - Pandiri, M; Freeman, J
Abstract: Casestudy : Acquired cystic disease-associated renal cell carcinoma (ACD-RCC) is a relatively recently recognized subtype of RCC. Although much less common than clear cell RCC and papillary RCC, it is the most common tumor occurring in patients with end-stage renal disease (ESRD) and acquired cystic disease (ACD). The tumor is said to occur exclusively in patients with acquired cystic disease, most commonly in patients undergoing long- term dialysis. We report a case of a 67-year-old male with stage IV chronic kidney disease due to membranous glomerulonephritis for 6 years with no history of dialysis and without a history of acquired cystic disease. The patient presented with left lower quadrant pain. On imaging, an enhancing exophytic mass was noted in the left kidney. Partial nephrectomy was performed, demonstrating a unifocal 2.2 cm nodular mass diagnosed as ACD-RCC. Microscopically, the tumor revealed intracystic papillary growth, focal cytoplasmic vacuoles (sieve-like growth) with involvement of perinephric adipose tissue by the tumoral cysts. Immunohistochemical staining revealed tumor cells positive for CD10, MIT/113, MPAX8, AMACR, and negative for CK7 and CD117. This immunophenotype supports the diagnosis of ACD-RCC (although itis not specific). Although the patient lacks a clinical history of dialysis and no intratumoral oxalate crystals were noted, the morphological findings and immunohistochemistry support the diagnosis of ACD-RCC, with concurrence by outside expert opinion. In summary, we present this unusual case of ACD-RCC to emphasize the awareness of this entity when considering the differential diagnosis of RCC in adult patients with chronic kidney disease, and specifically distinguish it from the close differential of papillary renal cell carcinoma.